Thrombin generation as a predictor of outcomes in patients with non-traumatic intracerebral hemorrhage - Lóczi, Linda; Orbán-Kálmándi, Rita; Árokszállási, Tamás; Fekete, István; Fekete, Klára; Héja, Máté; Tóth, Judit; Csiba, László; Bagoly, Zsuzsa (Frontiers in Neurology, 2022)
Background Non-traumatic intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes and leads to a higher rate of mortality as compared to ischemic strokes. We aimed to find out whether the thrombin generation assay (TGA) could predict outcomes in patients with ICH. Patients and methods In this prospective, observational study, 87 consecutive patients with ICH and 164 healthy controls were included. Computed tomography (CT), detailed clinical investigation, and laboratory investigations were performed from patients on admission. TGA was performed using stored platelet poor plasma obtained on admission. Lag time, endogen thrombin potential (ETP), peak thrombin, and time to peak parameters were calculated. Short- and long-term outcomes of ICH were defined at 14 days and 3 months post-event according to the NIHSS and the modified Rankin Scale (mRS), respectively. Results Peak thrombin was significantly higher in patients as compared to controls (397.2 ± 93.9 vs. 306 ± 85.3 nM, p < 0.0001). Lag time, ETP, and time to peak parameters showed a significant positive correlation with CRP in both groups. In patients with worse long-term functional outcomes, peak thrombin was significantly higher as compared to those with favorable outcomes [mRS 2–6 median: 402.5 (IQR:344.8–473.8) vs. mRS 0–1: 326.4 (294.2–416.1) nM, p = 0.0096]. Based on the statistically optimal threshold of 339.1 nM peak thrombin, the sensitivity and specificity of this parameter to determine mRS 2–6 as an outcome were 80.8 and 64.7%, respectively. In a binary logistic regression model including age, sex, BMI, smoking status, NIHSS on admission, D-dimer, and peak thrombin (>339.1 nM), only NIHSS and the peak thrombin parameters remained in the model as significant, independent predictors of poor outcome. Lag time and time to peak showed a modest, significant negative correlation with intracerebral bleeding volume on admission (r = −0.2603, p = 0.0231 and r = −0.3698, p = 0.0010, respectively). During the follow-up of patients, estimated hemorrhage volumes on day 90 showed significant positive association with the ETP and peak thrombin parameters (r = 0.3838, p = 0.0363 and r = 0.5383, p = 0.0021, respectively). Conclusion In patients with ICH, TG was increased as compared to healthy controls, which might be explained by the presence of higher inflammatory parameters in patients. Peak thrombin measured on admission might be a useful tool to predict outcomes in patients with ICH.